2019
DOI: 10.1186/s12937-019-0459-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pattern, dietary total antioxidant capacity, and dyslipidemia in Korean adults

Abstract: Background Abnormal diet is considered to be an important risk factor for dyslipidemia. However, so far, most studies have focused on the association between single factors only, such as specific nutrients, foods, or dietary patterns, and dyslipidemia risk. This study aimed to examine the association of the joint interaction between dietary pattern and dietary total antioxidant capacity (TAC) with dyslipidemia. Methods We performed a dietary pattern analysis and calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 51 publications
2
42
0
1
Order By: Relevance
“…There are many risk factors for dyslipidemia including genetic factors, hormonal abnormalities, and lifestyle factors. A diet especially high in fat is believed to be one of the greatest risk factors for the development of dyslipidemia [ 23 ]. Normally, pancreatic lipase is a key enzyme that hydrolyses ester linkages of triglyceride [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many risk factors for dyslipidemia including genetic factors, hormonal abnormalities, and lifestyle factors. A diet especially high in fat is believed to be one of the greatest risk factors for the development of dyslipidemia [ 23 ]. Normally, pancreatic lipase is a key enzyme that hydrolyses ester linkages of triglyceride [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study, the rice-oriented pattern was significantly increased prevalence of dyslipidemia in Korean adults men (OR = 1.58, p for trend = 0.0042, for hypertriglyceridemia, OR = 1.43, p for trend = 0.0015, for low HDL-cholesterol) and women (OR = 1.29, p for trend = 0.0020, for low HDL-cholesterol) using Korea National Health and Nutrition Examination Survey [ 35 ]. Another cross-sectional study showed that “oil, sweet, fish and other vegetables” dietary pattern and “grain, bean, nuts, vegetables and fruits” dietary pattern were lower risk of hypertriglyceridemia prevalence (OR = 0.73, p < 0.001 and OR = 0.88, p = 0.009, respectively) [ 7 ]. The Taiwan cross-sectional study showed similar results to our study, the vegetable-fruits-seafood dietary pattern (high intake of vegetables, vegetables with oil or dressing, fruits, seafood, legumes, soy products, and rice or flour products) decreased hypercholesterolemia risk (OR = 0.89) and dairy-complex carbohydrate dietary pattern (high intake of dairy products, milk, root crops, jam or honey, and whole-grain) decreased hypertriglyceridemia (OR = 0.82) in young and middle-aged Taiwanese [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vegetarian dietary patterns have beneficial effects on CVD [ 5 ], and adherence to healthy eating patterns have been associated with a lower risk of developing CVD in three large prospective cohort studies [ 6 ]. Additionally, several cross-sectional studies conducted to investigate an association between dietary patterns and dyslipidemia [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ninety-six articles were additionally excluded because of the following reasons: inappropriate exposure and/or outcome (n=62), unrelated methodology (n=14), unrelated population (n=6), and overlapping study population (n=14). Therefore, 62 studies, 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 including 42 cross-sectional, 3 case-control, and 17 cohort studies, were finally included in the systematic review and meta-analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%